ANALISIS STRATEGI PENGEMBANGAN UMKM DALAM UPAYA OPTIMASI PENJUALAN (STUDI KASUS WARUNG SUKAPURA) - Adinda Zahra Afiffah; Najla Salsabilla Zelyantie; Indra Saputra; Rafael Aginta S. Brahmana; Zida Naela Salsabilla; Muhammad Nadif (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the development strategy of the UMKM Warung Sukapura to enhance its business progress using a qualitative method with SWOT analysis, the 4P Marketing Mix, operational and financial conditions, as well as external analysis through PESTEL and Porter's Five Forces. Data was obtained through observation and interviews. The results of the study indicate that the strategic location is an advantage, while the main challenges faced by Warung Sukapura include a large number of unsold and expired products, limited profit margins, fluctuating sales due to unsold products, and competition from nearby stores. Government policies such as the increase in VAT and inflation also affect operations. Recommendations include the implementation of technology-based inventory management, product diversification with an eco-friendly focus, optimization of digital marketing, business legality, and collaboration with local partners to expand networks and competitiveness. This study provides practical insights for UMKM to face local business challenges and achieve sustainable growth.